The economics of international airline transport - Peoples, James (Emerald, 2014)
This volume provides in depth analyses of: changes in international air transportations legal environment; airline companies market behavior in this new environment; trade growth in response to changing airline market behavior; and examination of the external costs and benefits associated with growth in international air transportation.
Keywords: Aeronautics, Commercial -- Freight.; elektronické knihy; electronic books